PENINGKATAN USAHA “KERUPUK CAK MAKIN” DI KABUPATEN MOJOKERTO (PENGABDIAN KEPADA MASYARAKAT UNTUK PENDAMPINGAN USAHA MIKRO KECIL DAN MENENGAH) - Suharnanik Suharnanik; Ahmad Sufaidi; Sucahyo Tri Budiono; Yudi Harianto (Buletin Abdi Masyarakat, 2021)
This community service planning is carried out to provide online marketing training to MSMEs (Micro, Small, and Medium Enterprises) "Kerupuk Cak Makin". Our task to train marketing to MSMEs is very important because based on previous surveys, crackers are only marketed traditionally, by relying on several retail traders who come, such as middlemen. The methods used in this assistance are: 1) researching to determine the right online marketing, 2) making tutorials on how to do online marketing, 3) making product labels, and 4) making packaging to advertise online. This activity was carried out in a study based on the problem conditions experienced by small and medium business assisted partners located in Klinterejo Village, Sooko District, Mojokerto Regency. Among people who are experiencing the Covid 19 disaster, efforts are needed to survive and improve their business products, therefore we and the team are trying to make it happen through marketing assistance through online media. This community service looks at the problems faced by small and medium entrepreneurs that occurred in the era of covid 19, while the social, economic, and cultural impacts are predicted to experience changes from before, which of course needs to be managed and updated, ways and methods in developing businesses so that small entrepreneurs able to survive and develop their business.Keywords: Product Packaging, Online Marketing, Kerupuk Trader.